Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Differentiate respect to $x$

I did it,

but the answer is $1-\frac{x}{\sqrt{1-x^2}}$


share|cite|improve this question
You know how to use the chain rule, I suppose. – J. M. Apr 29 '12 at 10:58
yea. $u=(1-x^2)^\frac{1}{2}$ and $y=u^\frac{1}{2}$ , it is right? – Sb Sangpi Apr 29 '12 at 11:03
up vote 1 down vote accepted

If you have a function f(x):

$$f(x) = g(x)^m$$

then the derivative of f(x) with respect to x is:

$${df \over dx}(x) = m \times g(x)^{(m-1)} \times {dg \over dx}(x)$$

where ${dg \over dx}(x)$ is the derivative of g(x) with respect to x.

So, if you have:

$$f(x) = (1-x^2)^{1 \over 2}$$

then the derivative of f(x) with respect to x is:

$${df \over dx}(x) = {1 \over 2} \times {(1-x^2)}^{-{1 \over 2}} \times -2x = - {x \over \sqrt {1-x^2}}$$

More generally, chain rule works when you have $f(x) = h(g(x))$ then ${df \over dx}(x) = {dh \over dx}(g(x)) \times {dg \over dx}(x)$.

In your particular example, $h(x) = x^{1 \over 2}$ and $g(x) = 1-x^2$. So ${dh \over dx}(x) = {1 \over 2} \times x^{-{1 \over 2}}$ and ${dg \over dx}(x) = -2x$.

Therefore putting it all together gives ${df \over dx}(x) = {1 \over 2} \times (1-x^2)^{-{1 \over 2}} \times -2x$

share|cite|improve this answer

The function $\sqrt{1-x^2}$ actually is a composite function consisting of: $$f(x)=\sqrt{x} \ and \ g(x)=1-x^2 \ with \ f'(x)=\frac{0.5}{\sqrt{x}}, g'(x)=-2x$$ Your function is $f(g(x))$ and therefore its derivative according to the chain rule is: $$\frac{d(f(g(x))}{dx}=f'(g(x))\cdot g'(x)=\frac{0.5}{\sqrt{1-x^2}}\cdot(-2x)=\frac{-x}{\sqrt{1-x^2}}$$

share|cite|improve this answer

If $y=\sqrt{1-x^2}$, then $y$ is the upper half of the unit circle $x^2+y^2=1$. An arbitrary point $(x,y)$ on this circle has radial slope $\frac{y}{x}$, and the tangent slope is the negative reciprocal; that is, $$ y'=\frac{dy}{dx}=-\left(\frac{y}{x}\right)^{-1}=-\frac{x}{y} $$ without even needing to use the rules of calculus! If we want to use those rules, then we do instead $$ \eqalign{y' &=\frac{d}{dx}\left(1-x^2\right)^{1/2}\\ &=\frac12\left(1-x^2\right)^{-1/2}\frac{d}{dx}\left(1-x^2\right) \qquad\text{power & chain rules}\\ &=\frac12\cdot\frac{-2x}{\left(1-x^2\right)^{1/2}}\\ &=\frac12\cdot\frac{-2x}{\left(1-x^2\right)^{1/2}}\\ &=\frac{x}{y}\\ } $$ Finally, the answer to your problem is then $$ \frac{d}{dx}\left(x+y\right) =\frac{dx}{dx}+\frac{dy}{dx} =1+y' =1-\frac{x}{y} $$ or, equivalently, $$ 1-\frac{x}{y} =1-\frac{x}{\left(1-x^2\right)^{1/2}} =\frac{\left(1-x^2\right)^{1/2}-x}{\left(1-x^2\right)^{1/2}} =1-x\left(1-x^2\right)^{-1/2} \,. $$

share|cite|improve this answer

To differentiate $\sqrt{1-x^2}$

let $g(x)= 1-x^2$

now we have to differentiate $(gx)^{\frac{1}{2}}$

$\frac{d}{dx} (gx)^{\frac{1}{2}}=\frac{1}{2}(gx)^{\frac{-1}{2}}.g'(x)$

plug in the terms to get $-\frac{x}{\sqrt{1-x^2}}$



share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.